Ana's Story - Bush, Jenna; Nang Chan Yeema (New York, USA HarperCollins Publishers, 2007)
A story of courage, hope, and devotion. This book is based on the story of Ana's childhood and adolescence as she told it to me. It is a mosaic of her life, using words instead of shards of broken tile to create an image of her past and a framework for her future.
Keywords: Young Adult